Pendampingan Belajar Siswa dalam Pembelajaran Al-Qur'an untuk Menumbuhkan Karakter Disiplin di MI Miftahul Islam Paiton - Listrianti, Feriska; Widat, Faizatul (Al-DYAS, 2024)
The Al-Qur'an learning assistance program at MI Miftahul Islam Paiton was conducted to enhance students' understanding of the Al-Qur'an and develop their discipline. This topic was chosen due to the importance of Islamic religious education in shaping students' character and morals. The methods used in this community service included intensive learning and evaluation through pre-tests and post-tests. The results showed a significant improvement in students' understanding, with an average post-test score increase of 32.2 points. Additionally, there were positive changes in students' discipline in performing religious duties and adhering to school rules. The conclusion of this program is that Al-Qur'an learning assistance is effective in improving students' understanding and discipline. This finding is significant as it demonstrates that the right learning methods can have a substantial positive impact on Islamic religious education.